Virtual prototyping of hydraulic systems - Xiang, Wei (2008)
This thesis aims to use advanced modeling and simulation techniques, distributed artificial intelligence, virtual reality, and facilities for e-commerce to enhance the virtual prototyping process for hydraulic systems.